Microbial Keratinases: Enzymes with Promising Biotechnological Applications - Vidmar, Beti; Vodovnik, Maša (Food technology and biotechnology, 2018)
Keratin is a complex and structurally stable protein found in human and animal hard tissues, such as feathers, wool, hair, hoof and nails. Some of these, like feathers and wool, represent one of the main sources of protein-rich waste with significant potential to be transformed into value-added products such as feed, fertilizers or bioenergy. A major limitation impeding valorization of keratinous substrates is their recalcitrant structure and resistance to hydrolysis by common proteases. However, specialized keratinolytic enzymes produced by some microorganisms can efficiently degrade these substrates. Keratinases have already found a purpose in pharmaceutical, textile and leather industries. However, their wider implementation in other processes, such as cost-effective (pre)treatment of poultry waste, still requires optimization of production and performance of the available enzymes. Here we present a comprehensive review covering molecular properties and characteristics of keratinases, their classification, traditional and novel approaches in discovery of novel enzymes, production, characterization, improvement and biotechnological applications.